Entry and Competition in Concentrated Markets - Bresnahan, Timothy F.; Reiss, Peter C. (Journal of Political Economy, 1991)
This paper proposes an empirical framework for measuring the effects of entry in concentrated markets. Building on models of entry in atomistically competitive markets, the authors show how the number of producers in an oligopolistic market varies with changes in demand and market competition. These analytical results structure the authors' empirical analysis of competition in five retail and professional industries. Using data on geographically isolated monopolies, duopolies, and oligopolies, they study the relationship between the number of firms in a market, market size, and competition. The authors' empirical results suggest that competitive conduct changes quickly as the number of incumbents increases. Copyright 1991 by University of Chicago Press.